Unraveling the link between agricultural patterns and dust storm occurrence in Mesopotamia - Hossein Hashemi; Abdulhakim M Abdi; Amir Naghibi; Pengxiang Zhao; Sara Brogaard; Ali Torabi Haghighi; Ali Mansourian (Environmental Research Letters)
Dust storms have been an increasing concern in the Middle East. Severe drought events and human activities, particularly water and land management, have led to emerging dust sources in the last few decades. This study combines spatio-temporal maps of land susceptibility to dust storm incidence with agricultural land use change data to examine the link between farming patterns and dust storm generation in the Tigris and Euphrates Basin from 2000 to 2021. Farmland and bare ground trends depend heavily on water availability, affecting land susceptibility to dust storms. We observed a direct connection between cropping regimes and high land susceptibility to becoming a dust source. Our analysis found no significant correlation between low to intermediate dust storm source (DSS) susceptibility and bare ground trends. However, we found a positive correlation between highly susceptible land and areas where bare ground showed an increasing trend, including the lands that were abandoned for more than 50% of the study period. Among the farming patterns, i.e. single and double cropping, single cropping is more prone to DSS occurrence, underscoring the importance of year-round vegetation cover and effective water management. The disturbed lands, particularly those abandoned post-cropping, show higher susceptibility to DSS incidence. Between 2008 and 2012, dust sources and land susceptibility increased substantially, alongside a significant rise in bare ground, possibly due to severe drought. We highlight cases where changes in farming patterns and land abandonment contribute to the increased or decreased susceptibility of land to being a DSS, as well as consistent susceptibility in the cases where there is no land use change. Given the broad geographical scope of the study, this research underscores the need for further investigation, combining field measurements with remote sensing to obtain a more detailed picture of the link between farming patterns, land abandonment, and dust storms.